STUDI PENGARUH TIDAK BEROPERASINYA PLTSa SUWUNG TERHADAP PROFIL TEGANGAN PADA PENYULANG SERANGAN - Endrawadi, Gede; Sukerayasa, I Wayan; Ariastina, Wayan Gede (Jurnal SPEKTRUM; Vol 5 No 2 (2018): Jurnal SPEKTRUMDO - 10.24843/SPEKTRUM.2018.v05.i02.p38, 2018)
The power plant with renewable energy sources is needed to reduce the pollution. One of this kind is in Bali, that is PLTSa (Garbage Power Plant) Suwung. However, PLTSa Suwung is no longer operating for now. PLTSa Suwung is connected with Serangan feeder, this connection named Distributed Generation. When PLTSa Suwung doesn’t operate, it will affect the Serangan feeder’s voltage profile. The change of voltage profile will be analyzed with EDSA Technical 2000 Service Pack 3.5 software. The research will give five scenarios with different electrical power supply from each scenario. The gap of the voltage profile between scenario 1 (100% power supply from PLTSa) and scenario 5 (0% power suplly from PLTSa) is 0,0079% for medium voltage bus and 0,0062% for low voltage bus. This small gap shows that the connected PLTSa Suwung doesn’t give effect to voltage profile of Serangan feeder.